2016
DOI: 10.3390/molecules21121677
|View full text |Cite
|
Sign up to set email alerts
|

The Traditional Chinese Medicine DangguiBuxue Tang Sensitizes Colorectal Cancer Cells to Chemoradiotherapy

Abstract: Abstract:Chemotherapy is an important treatment modality for colon cancer, and concurrent chemoradiation therapy (CCRT) is the preferred treatment route for patients with stage II and III rectal cancer. We examined whether DangguiBuxue Tang (DBT), a traditional Chinese herbal extract, sensitizes colorectal cancer cells to anticancer treatments. The polysaccharide-depleted fraction of DBT (DBT-PD) contains greater amounts of astragaloside IV (312.626 µg/g) and ferulic acid (1.404 µg/g) than does the original fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…In our previous study, we determined that the amount of active ingredient in 2.6 g DBT decoction was equal to 0.3 g DBT-PD [ 21 ]. We evaluated the antitumor effect of both DBT and DBT-PD, and found that both DBT and DBT-PD inhibited the growth of colorectal adenocarcinoma in vivo (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, we determined that the amount of active ingredient in 2.6 g DBT decoction was equal to 0.3 g DBT-PD [ 21 ]. We evaluated the antitumor effect of both DBT and DBT-PD, and found that both DBT and DBT-PD inhibited the growth of colorectal adenocarcinoma in vivo (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous publication, the treatment of 10 mg/mL DBT-PD inhibited the growth of CT26 adenocarcinoma cells and sensitized the cells to chemoradiotherapeutic effects [ 21 ]. The mechanism of DBT-PD-induced CT26 cell death was found to be autophagy-associated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations